Treatment of Osteochondral Lesions of the Talus: An Evidence-based Opinionated Review. Issue 4 (December 2020) - Cong, Guang-Ting; Chinnakkannu, Karthikeyan; Krishnamoorthy, Vignesh P.; Di Lenarda, Luca; Mikhail, Christopher M.; Vulcano, Ettore
Abstract : Osteochondral lesions of the talus (OLTs) are a much-discussed topic in foot and ankle surgery due to their refractive nature to therapy. OLTs include fractures of the talar osteochondral surface from acute trauma or chronic repetitive injury, and their chronic subset in young patients conventionally referred to as osteochondritis dessicans. OLTs do not tend to heal well, and their treatments remain only moderately successful without an obvious superior method. The purpose of this review is to summarize the treatment of OLTs using current available literature and provide an opinionated preferred treatment algorithm. Level of Evidence: Diagnostic Level V. See Instructions for Authors for a complete description of levels of evidence.